GIGANTIC PERICARDIAL CYST CAUSING PALPITATIONS - CASE REPORT - Marcin Schulz; Alexander Suchodolski; Anna Kowal; Magdalena Królikowska; Jan Głowacki; Mariola Szulik (International Journal of Innovative Technologies in Social Science, 2025)
Pericardial cysts are rare mediastinal tumors, often asymptomatic but potentially causing cardiovascular symptoms through compression of adjacent structures. We present the case of a 63-year-old woman with an incidentally detected mediastinal cyst adjacent to the right atrium. Initially asymptomatic, she later developed palpitations, dyspnea, and exercise intolerance. Imaging revealed significant compression of the right atrium and valvular regurgitation. Surgical intervention included mitral valve repair, cyst excision, and drainage of exudative fluid. Histopathology confirmed a pericardial cyst. Postoperative follow-up demonstrated normal valve function and resolution of symptoms. This case highlights the importance of timely surgical management of symptomatic pericardial cysts to prevent cardiac complications. Video A. Transthoracic echocardiography (TTE), 4-chamber view, showing a fluid-filled lesion near the right atrium. Watch video